The timing of mergers along the production chain, capital structure, and risk dynamics - Tarsalewska, Monika (Journal of Banking & Finance, 2015)
I demonstrate that the timing of vertical mergers is generally dependent on industry characteristics. My predictions are consistent with empirically observed patterns of vertical mergers. I show that merger activity during economic upturns tends to be motivated by operating efficiencies, while merger activity during economic downturns tends to occur as a means of keeping production chain operational. Mergers allow firms to capture synergies and improve efficiencies in order to survive economic contractions. The pricing framework implies that a vertical merger decision usually reduces risk during two different economic states.